Clerical maintenance. The material situation of state administration officials in the Russian Empire in the 19th century - Kowalik, Jolanta (Perspektywa stołu, 2023)
The world of government officials of the Russian Empire was full of legal regulations. From the start of the career path (which had its course according to the rank table), to the outfit and the salary of the employee, all these aspects had to be approved by the tsar himself. The increase in the number of civil service in the Russian Empire in the nineteenth century was not proportionate to the increase in state spending on office administration. This resulted in low salaries, especially for employees who came in large number offices to ministries and central offices. Their barely ‘subsistence’ payments ensured only the minimum necessary for the living, and therefore the expenses for basic means of life necessities, including food, were also modest and often did not satisfy the basic physiological needs of a human being.However, officials of higher positions taking up ministerial or provincial posts enjoyed different material situation. Their salary allowed them to lead a more affluent standard of living, which also involved consumption of varied meals, not only at home, but also in restaurants, clubs and parties organized by them.Research on the cuisine of officials of the Russian Empire in the nineteenth century will become a pretext to trace their everyday living conditions and costs of living, which will prove the prevailing economic inequalities in this social group. The analysis of the topic will be carried out on the basis of available archival sources, memoirs and literature.